Assessing the Relationship between Organizational Climate and Nurses\' Job Motivation in Selected Army Hospitals of Tehran City - Nader Markazi moghaddam; Reyhaneh Rahmati; Mojgan Mohammadimehr; Ebadollah shiri; sanaz zargar balaye jame (Tehran University of Medical Sciences, 2017)
Background: Beside qualified and capable nursing personnel, nursing care development requires motivated nurses to work in an appropriate environment. This study aimed  at determining the relationship between organizational climate and nurseschr('39') job motivation in selected Army hospitals of Tehran city in 2015. Materials and Methods: In this study was a descriptive -analytical and cross sectional one. The sample size consisted of 340 employed nurses in hospitals with at least one year work experience which were stratified randomly selected based on work experience among four army hospitals in Tehran. Data were collected using two questionnaires including job motivation and organizational climate. In order to data .analysis, descriptive and analytical tests such as Pearson correlation coefficient were utilized. Results: One hundred and eighty nine of participants (55.4%) were female. Mean age of nurses' average was 32.22 ±9.8 years. More than half of nurses had evaluated group spirit as high level and hindrance, engagement, intimacy, consideration, spacing, thrust and production emphasis as moderate level. There was a direct significant relationship between all components of job motivation and engagement, intimacy, consideration, spacing, thrust and production emphasis (P<0.05). Furthermore, mental and official components of job motivation had an inverse significant relationship with hindrance component respectively (P=0.014, P=0.019). Conclusion: Regarding the relationship between all components of the organizational climate with job motivation, attempt to improve these components will have significant impact on motivation improvement, reducing absenteeism and job dissatisfaction.